Is Participation in Social Organizations an Alternative to Improve Household Economic Welfare in Chile? - Salazar, Cesar (Estudios de Economía, 2016)
This research aims to find the determinants of participation on social organizations in Chile through a social capital approach, as well as to evaluate the existence of a positive effect between participation and household welfare. In the case of economic and local organizations several regressions for participation and income were run. Due to the existence of endogenity of income in participation equation, it was estimated a simultaneous model for recreational organizations. The proposed model includes Two Stage Probit Least Squares estimates suitable to correct for simultaneity bias when one of the variables is continuous and the other is dichotomous. Econometric results point out that age, schooling, house ownership, place of residence and individual perception of both social intercourse and safety in their neighborhoods have a meaningful effect on participation. The study also reported on the positive effect between participation in economic organizations and household welfare.